1980
DOI: 10.1182/blood.v55.1.124.124
|View full text |Cite
|
Sign up to set email alerts
|

Lipid composition of freshly prepared and stored platelet concentrates

Abstract: To evaluate the possibility that changes in lipid composition might be related to the functional lesion that develops when platelets are stored as concentrates for several days, we measured lipid constituents of platelets in freshly prepared concentrates and in concentrates stored for 72 hr at 4 degrees C or at 20 degrees C under standard blood banking conditions. At 20 degrees C, but not at 4 degrees C, platelets lost about 15% of total cholesterol and 7%--11% of total phospholipid. The distribution of indivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
6
0

Year Published

1984
1984
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 45 publications
3
6
0
Order By: Relevance
“…This study investigates significant changes in lipid profiles of PLTs and plasma during storage of PLT concentrates. In agreement with previous studies we found a loss of total lipids in PLTs 8,9 that is accompanied by an increase of plasma lipids (Fig. 2) providing evidence for lipid cession due to microparticle shedding.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This study investigates significant changes in lipid profiles of PLTs and plasma during storage of PLT concentrates. In agreement with previous studies we found a loss of total lipids in PLTs 8,9 that is accompanied by an increase of plasma lipids (Fig. 2) providing evidence for lipid cession due to microparticle shedding.…”
Section: Discussionsupporting
confidence: 93%
“…The involvement of lipids in the development of the PLT storage lesion is also likely because of their hemostatic and structural importance and their chemical and physical lability 7 . Hamid and colleagues 8 and Okuma and colleagues 9 found a loss of both cholesterol and phospholipids during PLT storage. The mechanisms behind the lipid loss are mainly microvesiculation and lipid peroxidation 7 .…”
mentioning
confidence: 99%
“…In the 1980s, it was shown that the majority of AA is incorporated into phospholipids as part of the phospholipid bilayer in platelets. They found in platelet concentrates, isolated by the platelet‐rich plasma method, that 45% of AA is part of phosphatidylinositol (PI) phospholipids while ~ 16% is present in phosphatidylcholine . During 3 days of platelet storage, ~10% of total phospholipid was lost and released into the plasma storage media, while the content of individual phospholipids remained unchanged …”
Section: Thromboxane and Aa Metabolism During Platelet Storagementioning
confidence: 91%
“…Furthermore, a significant progressive decrease in haemostatic properties occurs, as evidenced by a decreased platelet aggregation response, decreased adenine nucleotide concentration, collection‐ or storage‐induced activation, loss of expression or affinity of surface receptors, activation of complement, and/or a change in the intracellular calcium concentration, leading to a cascade of events promoting platelet activation [6]. The majority of platelets undergo some degree of activation during procurement, processing or storage, leading to in vivo functional compromise [20–24,35].…”
Section: Discussionmentioning
confidence: 99%
“…Such lesions might be mediated by alterations in the biochemical or metabolic activity of the stored platelets, leading to an ultimate compromise in the in vitro function. For instance, irreversible changes in the shape of platelets, elevation of cytosolic calcium, assembly of filamentous actin, loss of activity of enzymes that play a critical role in signal‐transduction events, loss of or decrease in the number of available receptors, or loss of adenylate energy charge, are considered as storage‐induced lesions [19–24]. These lesions, singly or together, will be reflected in the viability and function of a platelet [5,25].…”
Section: Introductionmentioning
confidence: 99%